(untitled) (Journal of Human Sciences, 2025)
The importance of this study stems from its focus on a geographical region with its own unique geographical characteristics among the Libyan regions. It constitutes a wide area rich in diverse natural resources, ideal climatic characteristics, and the moderation it provides that human life seeks. Therefore, the Marj region is a destination for geographical researchers to uncover more of its characteristics, monitor their quantitative and qualitative pace, and shed light on climatic phenomena, their fluctuations, and the accompanying variations over time. The change that occurs over time is one of the basic characteristics when studying the elements of temperature and rain, and the rate of this change constitutes a major difference between the study areas. This difference can only be determined by studying the monthly, seasonal, and annual changes in the rates of the elements of temperature, wind, and rain in the region for a period of time sufficient for the study. This study addressed the Marj region from a climatic perspective, by studying the climate elements represented by temperature, wind speed and direction, and rainfall, during the period extending from (1975-2020 AD), with the aim of arriving at a climate classification consistent with the local conditions prevailing in this region. The researcher relied in presenting the details of the climate topic on many climate classifications, such as the classification: (Lange-de Marton-Sharaf-Jacobier-Combet-Koppen-Thornthwith-White).